Truancy Behavior in terms of the cause at SMP 13 Padang - Ope Yulia Regina; Marjohan Marjohan (Universitas Negeri Padang, 2021)
Truancy behavior is a form of undiscipline or student violation of school rules of conduct which will harm themselves and others such as leaving behind subject matter.In today's world, the phenomenon of truancy that occurs in the field is abundant. Based on observations and interviews that have been conducted with the school and the students themselves, truancy behavior is based on two factors, namely internal factors such as physical and psychological conditions, the second is external factors such as family and economy, society, and school. Therefore, the problem that will be examined in this research is,